Personal protection against biting insects and ticks (Parasite, 2011)
Recent events with the first cases of local transmission of chikungunya and dengue fever virus in southern France by Aedes albopictus, adding to the nuisance and potential vectors that can be encountered when traveling in tropical or sub-tropical countries, has shown the value of a reflection on the Personal protection against vectors (PPAV). It is seen during an outbreak of vector-borne disease, or simply because of nuisance arthropods, that our fellow citizens try to protect themselves individually by using an arsenal of resources available on the market. Yet most of these means have been neither checked for effectiveness or safety tests, however, essential. Travellers, staff on mission or assignment, are looking for specific information on how to protect themselves or their families. Health workers had at their disposal so far indications that vary widely from one source to another. Therefore it seemed important to the Society of Travel Medicine (SMV) and the French Society of Parasitology (SFP) to initiate a reflection on this theme. This reflection took the form of recommendations for good practice, following the outline established by the French High Health Authority (HAS). The aim was to gather all relevant information, verified and validated and the format to be used not only by health personnel (doctors, pharmacists, nurses), but also by travel agents and individuals. This document highlights the need to take into account the risk of vector-borne diseases, some deadly, and the benefit of various methods of personal protection. The choice of methods is clearly oriented towards those whose effectiveness has been proven and potential risks assessed. The paper finally proposes two decision trees based on the transmission type (day or night) and kind of stay (short or roaming, long and steady). It concerns travellers, but also expatriates, residents and nomads.